KIT D816V Positive Acute Mast Cell Leukemia Associated with Normal Karyotype Acute Myeloid Leukemia - Marta Lopes; Maria dos Anjos Teixeira; Cláudia Casais; Vanessa Mesquita; Patrícia Seabra; Renata Cabral; José Palla-García; Catarina Lau; João Rodrigues; Maria Jara-Acevedo; Inês Freitas; Jose Ramón Vizcaíno; et al. (Case Reports in Hematology)
Introduction. Mast cell (MC) leukemia (MCL) is extremely rare. We present a case of MCL diagnosed concomitantly with acute myeloblastic leukemia (AML). Case Report. A 41-year-old woman presented with asthenia, anorexia, fever, epigastralgia, and diarrhea. She had a maculopapular skin rash, hepatosplenomegaly, retroperitoneal adenopathies, pancytopenia, 6% blast cells (BC) and 20% MC in the peripheral blood, elevated lactate dehydrogenase, cholestasis, hypoalbuminemia, hypogammaglobulinemia, and increased serum tryptase (184 μg/L). The bone marrow (BM) smears showed 24% myeloblasts, 17% promyelocytes, and 16% abnormal toluidine blue positive MC, and flow cytometry revealed 12% myeloid BC, 34% aberrant promyelocytes, a maturation blockage at the myeloblast/promyelocyte level, and 16% abnormal CD2−CD25+ MC. The BM karyotype was normal, and the KIT D816V mutation was positive in BM cells. The diagnosis of MCL associated with AML was assumed. The patient received corticosteroids, disodium cromoglycate, cladribine, idarubicin and cytosine arabinoside, high-dose cytosine arabinoside, and hematopoietic stem cell transplantation (HSCT). The outcome was favorable, with complete hematological remission two years after diagnosis and one year after HSCT. Conclusions. This case emphasizes the need of an exhaustive laboratory evaluation for the concomitant diagnosis of MCL and AML, and the therapeutic options.